Catastrophic healthcare expenditure and its inequality for households with hypertension: evidence from the rural areas of Shaanxi Province in China - Yafei Si; Zhongliang Zhou; Min Su; Meng Ma; Yongjian Xu; Jesse Heitner (BMC, 2017)
Abstract Background China has been undergoing tremendous demographic and epidemiological transitions during the past three decades and increasing burden from non-communicable diseases and an ageing population have presented great health-care challenges for the country. Numerous studies examine catastrophic healthcare expenditures (CHE) worldwide on whole populations rather than specific vulnerable groups. As hypertension and other chronic conditions impose a growing share of the disease burden in China, they will become an increasingly important component of CHE. This study aims to estimate households with hypertension incurring CHE and its income-related inequality in the rural areas of Shaanxi Province. Methods Data were obtained from the National Household Health Service Surveys of Shaanxi Province conducted in 2013 and 13104 households were identified for analysis. The households were classified into three types: households with non-chronic diseases, households with hypertension only and households with hypertension plus other chronic diseases. CHE was measured according to the proportion of out-of-pocket health payments to non-food household expenditures and the concentration index was employed to measure the extent of income-related inequality in CHE. A decomposition method based on a probit model was used to decompose the concentration index into its determining components. Results The incurring of CHE of households with hypertension is at a disconcerting level compared to households with non-chronic diseases. Households with hypertension only and households with hypertension plus other chronic diseases incurred CHE in 23.48% and 34.01% of cases respectively whereas households with non-chronic diseases incurred CHE in only 13.33%. The concentration index of households with non-chronic diseases is -0.4871. However, the concentration index of households with hypertension only and households with hypertension plus other chronic diseases is -0.4645 and -0.3410 respectively. The majority of observed inequalities in CHE were explained by household economic status and having elder members. Conclusions The proportion of households incurring CHE in the rural areas of Shaanxi Province was considerably high in all three types of households and households with hypertension were at a higher risk of incurring CHE. Furthermore, there existed a strong pro-poor inequality of CHE in all three types of households and the results implied more inequality in households with non-chronic diseases compared with two other groups. Our study suggests that more concern needs to be directed toward households with hypertension plus other chronic diseases and households having elder members.